The synergistic effects of Nb/Mn and Sb/Mn on the microstructure and electrical characteristics of BaTiO3 based ceramics - Zivkovic, Lj M.; Mitic, V. V.; Paunovic, V. V.; Vracar, Lj M.; Stojanovic, B. D.; Peron, K. [UNESP]; Zagete, M. A. [UNESP] (Wiley, 2005)
The microstructure and dielectric properties of Nb-Mn or Sb-Mn codoped BaTiO3 compositions were investigated. Starting ceramics powders were prepared by Pechini method. The composites were sintered at 1310°C and 1330°C in an air atmosphere for two hours. The microstructure and compositional investigations were done with SEM equipped with EDS. Two distinguish microstructure regions are observed in Nb/0.05Mn doped BaTiO 3 ceramics sintered at low temperature. The first, large one, with grain sizes from 5-40 μm and the second region with small grain sizes from 1 to 5 μm. Sintering at higher temperature, independent of Mn content, enables to achieve a uniform microstructure with grains less than 6 μm. In Sb/Mn doped ceramics, for both sintering temperatures, bimodal microstructures with fine grained matrix and grains up to 10 μm is formed. The highest value of permittivity at room temperature and the greatest change of permittivity in function of temperature are observed in Nb/0.01Mn doped ceramics compared to the same ones in Sb/Mn doped ceramics. The greatest shift of Curie temperature towards lower temperature has been noticed in Sb/Mn BaTiO3 ceramics compared to others samples. In all investigated samples the dielectric loss after initially large values at low frequency maintains a constant value for f>3 kHz.
Keywords: Antimony; Barium titanate; Ceramic materials; Dielectric losses; Grain size and shape; Manganese; Microstructure; Natural frequencies; Niobium; Permittivity; Scanning electron microscopy; Sintering; Curie temperature; Pechini method; Sintering temperatures; Synergistic effects; Dielectric properties